Peningkatan Keterampilan Proses Sains dengan Menerapkan Model Pembelajaran InSTAD pada Pelajaran Fisika - Santi Yatnikasari; Muhammad Noor Asnan; Isnaini Zulkarnain (Jurnal Pengabdian Pada Masyarakat, 2021)
INCREASING SCIENCE PROCESS SKILLS BY APPLYING INSTAD LEARNING MODEL TO PHYSICS LESSONS. Science is the foundation of Natural Science. The essence of science can be developed through physics lessons. To improve learning outcomes and develop student creativity, one of which is the science process skills approach to train students to think independently, be independent, be scientific and be skilled in solving various problems, and be able to find concepts independently. The accuracy in choosing a learning model can help students to generate interest and increase learning outcomes. One learning model that can help students find concepts and use science process skills is the Inquiry Student Team Achievement Division (InSTAD) learning model, with the aim of producing a new syntax that can guide and require students to carry out investigations in group work. Community service activities are carried out at Madrasah Aliyah (MA) Al-Firdaus Samarinda. This activity was attended by 50 students who were divided into the control class and the experimental class. Activities begin with presentations, then group work, repetitions, tests and group awards. The results of the student evaluation in the experimental class with an average value of 75.2 with good criteria. Meanwhile, the control class was 64.5 with sufficient criteria. This shows that the application of the InSTAD learning model can improve the ability of the science process in physics lessons.